The Nigerian Integrated Early Childhood Development Policy: Perspectives on literacy learning - Linda Newman; Loveth Obed (South African Journal of Childhood Education, 2015)
Many scholars and researchers now have a broadened vision of literacy that encompasses the social practices that surround literacy learning. What accompanies this vision is a shift towards thinking that children, and their families, can contribute actively to literacy learning by drawing on their strengths and life experiences to create and draw meaning from a broad range of everyday sources. For many, reading and writing from print-based texts is no longer considered the only, or most desirable, avenue to literacy learning. It is now recognised that children’s social and cultural lives should be used as a resource for literacy learning. Using four literacy learning lenses, we examine the Nigerian National Policy for Integrated Early Childhood Development. These lenses are: collaboration with families, the role of educators, literacy-rich environments, and diversity and multimodality. Recent research around early literacy learning underpins our analysis to identify where the policy could more strongly refer to the role of families and educators and to argue that there is scope for greater attention to early literacy learning in the policy.